Taxonomic revision of Physalis in Mexico - Martínez, Mahinda; Vargas-Ponce, Ofelia; Zamora-Tavares, Pilar (Frontiers in Genetics, 2023)
Physalis (Solanaceae, Solanoideae) is an American genus of ca. 90 species with its diversity centered in Mexico. We recognize 61 species for the country for which we provide a general morphological description, an artificial key to determine species, and brief descriptions. We include distributions, habitats, diagnostic characters, phenology, and uses. Distribution maps and field photographs are also provided. We include conservation status as evaluated by the IUCN.